Drug metabolism and liver disease - Branch, Robert (Henry Stewart Talks, 2007)
Liver disease and drug clearance, Mechanistic explanations, Intact hepatocyte hypothesis, Sick cell theory, Sequential progressive model of liver disease, Viral liver disease, Alcoholic liver disease, Hepatocellular carcinoma, Liver transplantation
Archived at 2015/08/21